Optical remote spectral acquisition of elemental stoichiometry - Reeves, Jamie T.; Hasnain, Sarah S.; Nessel, Mark P.; Talbot, Ceara J.; Thomson, Eleanor R. (Frontiers in Ecology and Evolution, 2024)
Optical remote sensing (RS) enables the study of the elemental composition of Earth’s surface over broad spatial extents by detecting reflected electromagnetic radiation. Covalent bonds of macromolecular structures often reflect electromagnetic radiation at specific wavelengths, and in some cases relate to bonds of specific elemental identity. In other cases, interfering optical properties greatly impact the ability of RS to measure elements directly, but advances in statistical methods and the theoretical understanding of optical properties expand the capacity to quantify diverse elements in many systems. When applied under the framework of ecological stoichiometry, spatially and temporally explicit measurements of elemental composition permit understanding of the drivers of ecological processes and variation over space and through time. However, the multitude of available technologies and techniques present a large barrier of entry into RS. In this paper we summarize the capabilities and limitations of RS to quantify elements in terrestrial and aquatic systems. We provide a practical guide for researchers interested in using RS to quantify elemental ratios and discuss RS as an emerging tool in ecological stoichiometry. Finally, we pose a set of emerging questions which integrating RS and ecological stoichiometry is uniquely poised to address.